Autologous surface repair: autologous matrix-induced chondrogenesis and minced cartilage implantation - Stefan Schneider; René Kaiser; Bente Uterhark; Johannes Holz; Robert Ossendorff; Gian Salzmann (Elsevier, 2023)
ABSTRACT: Introduction: The treatment of cartilage damage remains challenging. There are several procedures described. Microfracturing is considered one of the most established procedures, but long-term results are unsatisfactory, especially for larger defects. Autologous matrix-induced chondrogenesis (AMIC), in which bone marrow-stimulated areas are covered with a membrane, has been introduced to address some of the limitations of microfracture with a number of long-term outcomes studies reporting satisfactory results. Minced cartilage implantation (MCI), in which cartilage tissue is minced and inserted into cartilage defects has also been shown to have satisfactory results at 5-year results, although longer-term results are still pending. Technique: Both procedures can be performed arthroscopically. In the AMIC procedure, bone at the base of the chondral lesion is debrided to the subchondral plate and a bone marrow stimulation or microfracture is performed. Arthroscopic fluid is drained and the area covered with a membrane and fixed using fibrin glue or stiches either arthroscopically or using a mini-open approach. In MCI, the defect is also first debrided. Cartilage tissue removed from the affected joint is then cut into small pieces. In the open procedure, this is done with a scalpel; in the arthroscopic procedure, it is done with a shaver. The tissue is then inserted into the defect and fixed using an allogeneic or autologous fibrin glue. Discussion: AMIC and the minced cartilage technique represent a relatively simple, safe and reproducible evolution of cartilage repair techniques. Long-term studies (up to 9 years) support the satisfactory outcomes of the AMIC procedure. Five-year results for the MCI procedure report a decrease in pain and improved function, but long-term results are awaited. Well-designed level 1 studies are now required to evaluate these techniques in the longer term.